Analysis of Student Perceptions of Teacher Quality and Learning Environment as Predictors of Learning Motivation in High Schools - Simbolon, Bintang R.; Jihan, Jihan; Susanti, Pipit Aprilia; Sukomardojo, Tekat; Rizqi, Vini (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Learning is an activity that is very important to carry out, especially for high school students. In practice, the student’s motivation often determines success in learning. Therefore, high school students’ motivation needs to be increased to study well. The researcher was then interested in seeing how high school students’ perceptions of teacher quality and learning environment affect their motivation to learn. This research will be carried out using a descriptive qualitative approach. The data to be used in this study comes from various research results and previous studies, which still have relevance to the discussion in this study. The results of this study then found that teacher quality can increase learning motivation for high school students. This is because a good teacher will make it easier for high school students to understand what they are learning, so learning motivation will increase even higher. Then a good learning environment can also increase high school students learning motivation. This is because, with a few distractions, students can focus on learning well. The learning process at home through e-learning often causes a learning environment full of distractions, so high school students learning motivation decreases extensively.